Sustaining job performance through technology acceptance with usage of whatsapp mobile application / Nor Hayati Kassim... [et al.] - Kassim, Nor Hayati; Mohamed Noor, Norlina; Ali, Jati Kasuma; Saleh, Juliza; Dealwis, Ceaser; Nurhisham, Muhamad Azim (Universiti Teknologi MARA Cawangan Sarawak, 2020)
Companies are now recognizing that their employees require a spectrum of mobile applications in order to achieve maximum efficiency at the workplace. Mobile applications such as WeChat, Twitter and WhatsApp via smartphones have become influential tools and extensively used by employees at the workplace. This state-of-the-art technology in communication has penetrated various fields, including routine administrative jobs at the workplace. The objective of this research is to investigate the acceptance of the WhatsApp mobile application for formal use among support staff at The Commission of the City of Kuching North, Sarawak (DBKU). Perceived usefulness, perceived ease of use and behavioral intention of the users in using WhatsApp are the variables measured for job performance. The researchers utilized convenience sampling, whereby a total of 105 employees from two departments participated in the investigation. Data was collected using a set of selfadministered questionnaires which was adapted from Davis. The findings revealed that perceived usefulness and perceived ease of use of WhatsApp as a means of communication were significant for job performance at DBKU. The employees felt more competent during their formal interaction Sustaining Job Performance through Technology Acceptance with Usage of Whatsapp Mobile Application 123 Sustaining Job Performance through Technology Acceptance with Usage of Whatsapp Mobile Application 122 at the workplace as less effort was needed while using WhatsApp. The existence of features which were user-friendly and easy operational functions helped to create positive attitudes when utilizing the application. Faster feedback, ease of use, and convenience were some of the reasons for the employees' willingness to use WhatsApp for communication at the workplace.